Phase Conversion of Ice‐Templated α‐Tricalcium Phosphate Scaffolds into Low‐Temperature Calcium Phosphates with Anisotropic Open Porosity. Issue 5 (24th May 2021) - Seifert, Annika; Groll, Jürgen; Weichhold, Jan; Boehm, Anne V.; Müller, Frank A.; Gbureck, Uwe
Abstract : Aligned porous non‐sintered and sintered a‐tricalcium phosphate (a‐TCP) scaffolds are prepared by ice‐templating and converted into the low‐temperature calcium phosphates calcium‐deficient hydroxyapatite (CDHA), brushite and monetite. This is achieved by hydrothermal treatment or incubation in phosphoric acid solution and has a high clinical potential due to the higher solubility of these phases. Further details can be found in the article, number 2001417, by Uwe Gbureck and co‐workers.